(untitled) (Research, Society and Development, 2022)
Objective: to map the nutritional care directed to adolescents and young adults submitted to laparotomy. Methodology: This is a scope review protocol, structured according to methodological guidelines of the Joanna Briggs Institute. Six databases will be used, with the use of Health Sciences Descriptors. The process of search, identification and evaluation of articles will be carried out by two independent evaluators, based on the assumptions established by the Joanna Briggs Institute, seeking to answer the following guide question: What nutritional care is directed to adolescents and young adults in the peri and postoperative laparotomy period? Literature published in any language, available online, in full text, without time and in any methodological design will be selected. The results will be grouped and arranged in tables, graphic models or textual categories, according to the information found in the final topics. A summary table containing the main results found with subsequent narrative discussion of the findings will be elaborated. The protocol was registered in the Open Science Framework, under registration nº osf.io/bd93k.